2011
DOI: 10.1007/s00737-011-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen replacement therapy on symptoms of depression and anxiety in non-depressive menopausal women

Abstract: The efficacy of estrogen replacement therapy (ERT) for mood disturbances associated with menopause has yet to be firmly established. The objective of this study was to investigate the efficacy of ERT for improving mood and anxiety of non-depressive postmenopausal women. This double-blind, randomized, placebo-controlled study involved two treatment groups: one receiving conjugated equine estrogens (CEEs; 0.625 mg/day) and the other placebo, for six cycles of 28 days each. Subjects were hysterectomized, healthy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
3
27
0
1
Order By: Relevance
“…On the contrary, the efficacy of oral ET in mood improvement is more questionable, as suggested by previous small trials 18,31<35 and further confirmed by more recent randomized controlled trials specifically focused on depressive symptoms in postmenopausal women. 42,43 Taken together, these results confirm the hypothesis that women's sensitivity to estrogens and changes in estrogen levels may be heightened during the menopausal transition but reduced in postmenopause. This may limit the optimal timing for ET to a temporal window during the perimenopausal period when women are also more vulnerable to depressive symptoms and disorders related to hormonal fluctuations.…”
Section: Gonadal Hormones and The Brainsupporting
confidence: 82%
“…On the contrary, the efficacy of oral ET in mood improvement is more questionable, as suggested by previous small trials 18,31<35 and further confirmed by more recent randomized controlled trials specifically focused on depressive symptoms in postmenopausal women. 42,43 Taken together, these results confirm the hypothesis that women's sensitivity to estrogens and changes in estrogen levels may be heightened during the menopausal transition but reduced in postmenopause. This may limit the optimal timing for ET to a temporal window during the perimenopausal period when women are also more vulnerable to depressive symptoms and disorders related to hormonal fluctuations.…”
Section: Gonadal Hormones and The Brainsupporting
confidence: 82%
“…HRT was not found to significantly impact the percentage of women endorsing clinically significant elevations in depressive symptoms. Similarly, an RCT of 76 hysterectomized euthymic postmenopausal women did not find an effect of treatment on mood or anxiety after randomization to six 28-day cycles of either conjugated equine estrogen (0.625 mg/day) or placebo [31].…”
Section: The Late Postmenopausal Periodmentioning
confidence: 97%
“…Similarly, androgen blockade therapy for prostate cancer treatment has been reported to increase anxiety, which was alleviated when treatment ended (Almeida et al, 2004). Although the nature of the relationship between these steroid hormones and anxiety level is not always consistent (Demetrio et al, 2011; Kiesner, 2011; Thomson and Oswald, 1977), they appear to exert anxiolytic effects in a number of different circumstances.…”
mentioning
confidence: 99%